The Bone—Vasculature Axis: Calcium Supplementation and the Role of Vitamin K - Wasilewski, Grzegorz B.; Vervloet, Marc G.; Schurgers, Leon J. (Frontiers in Cardiovascular Medicine, 2019)
Calcium supplements are broadly prescribed to treat osteoporosis either as monotherapy or together with vitamin D to enhance calcium absorption. It is still unclear whether calcium supplementation significantly contributes to the reduction of bone fragility and fracture risk. Data suggest that supplementation of post-menopausal women with high doses of calcium has a detrimental impact on cardiovascular morbidity and mortality. Chronic kidney disease (CKD) patients are prone to vascular calcification because of impaired kidney function, and thus as one of the many consequences impaired phosphate excretion. Calcium-based phosphate binders further increase risk on vascular calcification progression. In both bone and vascular tissue, vitamin K-dependent processes play an important role in calcium homeostasis and it is tempting to speculate that vitamin K supplementation might protect from detrimental effects of calcium supplementation. This review provides an update on current literature on calcium supplementation among post-menopausal women and CKD patients and discusses underlying molecular mechanisms of vascular calcification. We propose therapeutic strategies with vitamin K treatment to prevent or hold progression of vascular calcification as a consequence of excessive calcium consumption.